2011
DOI: 10.1016/j.joep.2011.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment duration and personality

Abstract: This paper focuses on the role personality traits play in determining individual unemployment duration. We argue that a worker's job search intensity is decisively driven by her personality traits, reflected in her propensity to motivate and control herself while searching for a job. Moreover, personality traits, in as far as they can be signaled to a potential employer, may also enhance the probability of receiving and accepting a job offer.For our econometric duration analysis, we use the well-accepted taxon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(108 citation statements)
references
References 26 publications
(21 reference statements)
4
97
0
4
Order By: Relevance
“…They find that individuals with higher scores on openness are more likely to experience more frequent unemployment spells. This might stem partly from selection into jobs with a higher probability of job loss or the possibility that open individuals are more likely to accept job offers that deviate from their previous positions and skill levels (Uysal and Pohlmeier, 2011). This suggests that unemployment or job loss might be caused by personality traits.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…They find that individuals with higher scores on openness are more likely to experience more frequent unemployment spells. This might stem partly from selection into jobs with a higher probability of job loss or the possibility that open individuals are more likely to accept job offers that deviate from their previous positions and skill levels (Uysal and Pohlmeier, 2011). This suggests that unemployment or job loss might be caused by personality traits.…”
Section: Previous Researchmentioning
confidence: 99%
“…Existing research shows that openness is associated with increased unemployment duration, which might partly stem from selection into more insecure jobs or the possibility that open individuals are more likely to accept job offers that deviate significantly from their previous position (Uysal and Pohlmeier, 2011;Viinikainen and Kokko, 2012). Studies in this stream of literature focus on unemployment experience, on the unemployment level in general, and on the duration of unemployment, which all might indicate potential channels of the effect of job loss on personality traits.…”
Section: Introductionmentioning
confidence: 99%
“…According to Uysal and Pohlmeier (2011), conscientiousness and emotional stability were associated with unemployment duration, which suggests that personality traits in workers can influence job-search intensity.…”
Section: Personality Traits and Labor Market Outcomesmentioning
confidence: 99%
“…However, Extraversion is negatively associated with entrepreneurship and entrepreneurial performance. Other studies have found that higher Conscientiousness, lower Agreeableness and lower Neuroticism are associated with better labour market success in terms of earnings, job performance and employment (Heineck 2010;Almlund et al 2011;Uysal and Pohlmeier 2011;Nandi and Nicoletti 2014). However, Extraversion seems to be positively associated with better labour market performance (Nandi and Nicoletti 2014).…”
Section: Introductionmentioning
confidence: 93%